Undetectable gadolinium brain retention in individuals with an age‐dependent blood‐brain barrier breakdown in the hippocampus and mild cognitive impairment. Issue 12 (1st December 2019) - Montagne, Axel; Huuskonen, Mikko T.; Rajagopal, Gautham; Sweeney, Melanie D.; Nation, Daniel A.; Sepehrband, Farshid; D'Orazio, Lina M.; Harrington, Michael G.; Chui, Helena C.; Law, Meng; Toga, Arthur W.; Zlokovic, Berislav V.
Abstract: Introduction: Blood‐brain barrier (BBB) breakdown is an early independent biomarker of human cognitive dysfunction, as found using gadolinium (Gd) as a contrast agent. Whether Gd accumulates in brains of individuals with an age‐dependent BBB breakdown and/or mild cognitive impairment remains unclear. Methods: We analyzed T1‐weighted magnetic resonance imaging (MRI) scans from 52 older participants with BBB breakdown in the hippocampus 19‐28 months after either cyclic or linear Gd agent. Results: There was no change in T1‐weighted signal intensity between the baseline contrast MRI and unenhanced MRI on re‐examination in any of the studied 10 brain regions with either Gd agent suggesting undetectable Gd brain retention. Discussion: Gd does not accumulate in brains of older individuals with a BBB breakdown in the hippocampus. Thus, Gd agents can be used without risk of brain retention within a ∼2‐year follow‐up to study BBB in the aging human brain in relation to cognition and/or other pathologies.